2020
DOI: 10.1186/s13006-020-00319-3
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding during the COVID-19 pandemic – a literature review for clinical practice

Abstract: Background The COVID-19 pandemic is disrupting normal life globally, every area of life is touched. The pandemic demands quick action and as new information emerges, reliable synthesises and guidelines for care are urgently needed. Breastfeeding protects mother and child; its health benefits are undisputed and based on evidence. To plan and support breastfeeding within the current pandemic, two areas need to be understood: 1) the clinical characteristics of COVID-19 as it applies to breastfeeding and 2) the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
1
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 43 publications
0
113
1
11
Order By: Relevance
“…The choice between rooming-in or mother-new born baby separation is important and the review of available cases showed that the avoidance of separation might be associated with a higher risk of late-onset neonatal SARS-CoV-2 infection. This is important since neonatal SARS-CoV-2 infections are more commonly acquired postnatal, through environmental exposure [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choice between rooming-in or mother-new born baby separation is important and the review of available cases showed that the avoidance of separation might be associated with a higher risk of late-onset neonatal SARS-CoV-2 infection. This is important since neonatal SARS-CoV-2 infections are more commonly acquired postnatal, through environmental exposure [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result of one systematic review shows that postpartum anxiety has negative impacts on breastfeeding initiation, duration, and exclusivity (22). Transmission of covid-19 as a respiratory virus via breast milk is not common even for mothers who tested positive (23). The properties of breast milk including anti-infective factors, as well as transferring of immunological competence and memory can protect the infant against infection disease (23).…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of covid-19 as a respiratory virus via breast milk is not common even for mothers who tested positive (23). The properties of breast milk including anti-infective factors, as well as transferring of immunological competence and memory can protect the infant against infection disease (23). Mother anxiety has an adverse physiological effect on breastfeeding due to maternal anxiety and stress can interfere with oxytocin releasing and milk ejection re ex.…”
Section: Discussionmentioning
confidence: 99%
“…Although not enough evidence supports SARS-CoV-2 transmission through breast milk [ [140] , [141] , [142] ], close contact during breastfeeding may contribute to the transmission of infection from mothers to their newborns [ 75 ]. Therefore, feeding of expressed mother’s milk should be considered to avoid the child’s contact with the COVID-19 infected mother [ 143 ].…”
Section: Management and Preventive Strategies: General Approaches And Special Considerationsmentioning
confidence: 99%